2019
DOI: 10.3390/cells8030214
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factors and the Regulation of Lipid Metabolism

Abstract: Oxygen deprivation or hypoxia characterizes a number of serious pathological conditions and elicits a number of adaptive changes that are mainly mediated at the transcriptional level by the family of hypoxia-inducible factors (HIFs). The HIF target gene repertoire includes genes responsible for the regulation of metabolism, oxygen delivery and cell survival. Although the involvement of HIFs in the regulation of carbohydrate metabolism and the switch to anaerobic glycolysis under hypoxia is well established, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
184
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(187 citation statements)
references
References 117 publications
(154 reference statements)
3
184
0
Order By: Relevance
“…PHDi-induced lipid accumulation in hPTEC was dependent on exogenous FA availability, which might imply that PHDi promoted lipid uptake. The import of extracellular FA into the cell is known to be increased by HIF-dependent upregulation of fatty acid binding proteins (FABP) 3, 4 and 7 (Mylonis et al 2019). Therefore, upregulation of FABP might also have a role in PDH-induced lipid accumulation in hPTEC, which should be investigated in further experiments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PHDi-induced lipid accumulation in hPTEC was dependent on exogenous FA availability, which might imply that PHDi promoted lipid uptake. The import of extracellular FA into the cell is known to be increased by HIF-dependent upregulation of fatty acid binding proteins (FABP) 3, 4 and 7 (Mylonis et al 2019). Therefore, upregulation of FABP might also have a role in PDH-induced lipid accumulation in hPTEC, which should be investigated in further experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the HIF pathway in the regulation of renal lipid metabolism has been intensively examined in ccRCC (Mylonis et al 2019). However, beyond tumor models, the effects of HIF on lipid metabolism in the kidney are largely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HTN induces vasoconstriction of small vessels and reduced microvascular density, which impairs tissue perfusion . In cultured cells and many organs, including the liver and islets, hypoxia and hypoxia‐inducible factors have been associated with altered lipid metabolism and intracellular lipid droplet accumulation . Several animal and cell culture studies have identified that intracellular lipid storage within islets causes a marked reduction in islet function, through inhibition of insulin production and secretion, as well as cellular toxicity .…”
Section: Discussionmentioning
confidence: 99%
“…64 In cultured cells and many organs, including the liver and islets, hypoxia and hypoxia-inducible factors have been associated with altered lipid metabolism and intracellular lipid droplet accumulation. [65][66][67][68] Several animal and cell culture studies have identified that intracellular lipid storage within islets causes a marked reduction in islet function, through inhibition of insulin production and secretion, as well as cellular toxicity. [41][42][43][44][45]69,70 Consequently, HTN may contribute to chronic tissue hypoxia resulting in lipid accumulation and islet dysfunction.…”
Section: F I G U R Ementioning
confidence: 99%